Co-created value influences residents' support toward the sporting event through the mediating mechanism of gratitude. Issue 1 (2nd January 2023) - Zhang, Jingxian (Cecilia); Byon, Kevin K.; Tsuji, Yosuke; Pedersen, Paul M.
ABSTRACT: Research question: The purpose of this study was to examine the effects of residents' co-created value on their intentions to support a sporting event through the mediating mechanism of gratitude. Research methods: Data were collected from residents' participating in a local recurring sporting event (Naha Marathon, n = 198) and an international recurring sporting event (New York Marathon, n = 229). Results and findings: The findings reveal that gratitude shows a strong positive impact on residents' event support intentions. Also, the results indicate gratitude is a mediating psychological mechanism that can explain the relationship between co-created value and residents' event support intentions. Implications: We provide insights into the important role of gratitude in understanding how co-created value and relationship marketing variables function together to influence residents' intentions to support recurring sport events. Also, findings of the current study assist in the understanding of resident-event relationships and contribute to the growing understanding of residents' support for recurring events.